Peran Guru Pendidikan Agama Hindu Dalam Menanamkan Filosofi Pendidikan Multikultural Bagi Siswa Hindu Di SMPN 2 Basarang Kabupaten Kapuas - I Gede Dharman Gunawan; Kadek Sukiada; I Ketut Subagiasta; I Gede Arya Juni Arta (Jayapangus Press, 2022)
This study aims to analyze the role of Hindu religious education teachers in instilling a philosophy of multicultural education for Hindu students at SMPN 2 Basarang, Kapuas Regency. Indonesia is a multicultural country consisting of different tribes, languages and religions. This diversity on the one hand is an advantage and wealth of the nation that must be maintained. But on the other hand, this diversity can be a potential for conflict in society. Therefore, an understanding of the nation's motto